Liberating Community-based Research: Rescuing Gramsci’s Legacy of Organic Intellectuals - Sousa, José Wellington (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2022)
This article aims to provoke a discussion around conceiving community members as community-based research facilitators and leaders of their own process of change. It argues this is possible by rescuing Gramsci’s legacy of organic intellectuals that is present in community-based research literature, particularly under the participatory research rubric. However, this perspective has been overshadowed by a strong emphasis on community-based research (CBR) as a collaborative research approach rather than a people’s approach for knowledge production that leads to social transformation. Furthermore, such a view of community-based research is fruitful within an adult education and social movement learning framework. In a sense, social movements provide an environment that facilitates critical consciousness and the formation of organic intellectuals and in which communities and academics learn to better engage in partnership for community-led social change. In this context, CBR is still a collaborative approach, but one led primarily by organic intellectuals.